Kebutuhan Air Tanaman untuk Penjadwalan Irigasi pada Tanaman Jeruk Keprok 55 di Desa Selorejo Menggunakan Cropwat 8.0 - Liliya Dewi Susanawati; Bambang Suharto (Balai Teknik Irigasi, 2017)
Keprok 55 (Citrus reticulate) is one of the horticulture commodities which are prioritized to be developed especially in Batu City, Malang. The main problem of Keprok 55 orange is water availability. Crop water requirement so far solely rely on rainfall which is erratic, particulary in the region of Selorejo. Therefore, proper irrigation management is needed, one of them is planning the crop water requirement. This study aims to plan and calculate needs of crop water requirement using Cropwat 8.0 software and evaluate the result with the actual condition. The research was conducted at orange orchard in Selorejo Village, Dau District, Malang Regency. This research uses quantitative descriptive analysis and data processing using Cropwat 8.0. The results showed that the total crop water demand (ETc) during the growth period was 971.90 mm with the highest actual evapotranspiration of the plants reached in October, the third period of 34.80 mm and the lowest in the third February of 19.70 mm. The result from Cropwat 8.0, are very helpful in determining the cropping season and the amount of irrigation for planning purpose. However, day to day operation must be conducted based on actual crop and rainfall condition to maintain soil moisture at appropriate level to support crop growth.